SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR OPTIMIZING THE TRAINING PROCESS IN YOUNG TRACK AND FIELD ATHLETES - Utepov Makhmud Daurkhanovich (Innovate Conferences, 2025)
This thesis examines the scientific and methodological foundations for optimizing the training process of young track and field athletes. Using the IMRaD structure, the study explores load regulation, biomechanical analysis, individualized training models, psychological preparation, and modern monitoring technologies aimed at enhancing performance, preventing injuries, and supporting long-term athletic development.